Australians underestimate social compliance with coronavirus restrictions: findings from a national survey - Zoe Leviston; Samantha K. Stanley; Iain Walker (Elsevier, 2022)
Abstract Objective: We assessed differences between Australians' perceptions of their own compliance with coronavirus restrictions and their perceptions of community compliance. Methods: We surveyed a national quota sample of 1,691 Australians in August and September 2020. Participants reported their level of compliance with coronavirus restrictions and estimated compliance from others in their state/territory. Results: Overwhelmingly, most people reported complying with restrictions. They believed their fellow community members were much less compliant. Age and other demographics were only weakly associated with self‐reported compliance and perceptions of others' compliance. Conclusions: The results are consistent with prevalent cognitive biases, including the tendency to believe one is better‐than‐average, and to more easily recall instances of deviances from social norms. Implications for public health: We recommend public health messaging avoids amplifying instances of social transgressions of coronavirus restrictions. Instead, the widespread nature of social compliance with restrictions across the country should be emphasised.